Dostęp przewoźników do portów lotniczych w Unii Europejskiej – aspekty prawne i ekonomiczne - Kociubiński, Jakub (Kwartalnik Prawa Publicznego, 2013)
From the air carrier’s standpoint, access to airport determines its scheduling and thus the overall competitiveness of the operation. At the same time with ever-increasing air traffic, demand for airport slots – times for take-off/landing – exceeds the current output. For this reason an efficient, transparent and nondiscriminatory system of slot allocation is a vital tool for maintaining sound competitive process. This paper provides an overview of the communautaire slot distribution system and its impact on the overall competitiveness and the structure of the market. The analysis takes its point of departure with the brief examination of the role of airport access for airline economics and then focus on the impact of competition between airport on financial performance of air operations and route structure. The next stage of scrutiny covers crucial issue of the legal status of the slot in the context of European regulatory system where secondary trading while officially endorsed is happening due to existing lex lacunae. Impact assessment of this regulatory regime with focus on the competition and regulatory remedies and with an outlook for possible reform concludes this paper.